Desenvolvimento motor e percepção de competência atlética: um estudo com crianças entre 8 e 10 anos da rede pública de ensino - Silva, Schelyne Ribas da (2009)
The objective of this research, of transversal delineation, was to investigate the level of motor competence, athletic perceived competence and nutritional status of scholars from 8 to 10 years of age and the possible relations among the variables.The study's sample was composed by 481 school students (250 boys and 231 girls) aged between 8 and 10 years, of the public teaching network from the city of the Maringa-PR. Were used as instruments: Ulrich's motor test (2000) Test of Gross Motor Development 2 (TGMD-2), the perceived competence questionnaire Pictorial Scale of Perceived Competence and Social Acceptance (HARTER, 1985), the evaluation of nutritional status (BMI) by the weight and stature, taking Cole (2000) as reference. For the statistical data analysis were used the descriptive analysis with median and Interquartilic Interval, absolute and relative frequency, and the tests: Shapiro-Wilk, Mann-Whitney, Qui-square, Fisher's Exact, Spearman's correlate and One-Way ANOVA analysis of variance with Bonferroni post hoc, adopting p<0,05. The results indicated that in general boys and girls were classified with very poor Motor Development. As for locomotion abilities the scores were similar between gender (3,0), in the object control abilities and motor quotient the boys presented higher scores in relation to girls (6,0-5,0; 67-64 respectively). Significant differences between gender were observed in the object control abilities (p=0,001) and motor quotient (p=0,000). In relation to age, younger boys and older girls demonstrated high scores in locomotion abilities (4,0-4,0 respectively) and in motor quotient (70-64 respectively). When verifying athletic perceived competence of the sample significant superiority was identified (p=0,015*) for the boys in relation to girls and when compared the ages was observed a decrease in scores with the increase of chronological age. In the nutritional status 25,6% of the sample presented overweight (14,3% of the boys and 11,3% of the girls). 9 years old boys (34%) and 10 years old girls (32,7%) showed higher percentage of overweigh in relation to the age lines. Significant associations were not identified between the variables. About the correlation the results showed low negative correlation, but significant, for the motor quotient with the BMI (-0,18*) only for masculine gender. When the sample was aggregated, low negative significant correlation fwas identified for motor quotient with the BMI (-0,14*) and low positive significant correlation for athletic perceived of competence with the locomotion abilities (0,10*). So it is concluded that motor stimulation provided to children of the study, seems to have been ineffective, so far, to improve the motor development, the real perceived of athletic competence and the nutritional status suitable to ages.